One-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction, preparation method thereof and application in room-temperature sodium-sulfur battery
Patent Information
- Application Number
- CN202611182993.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明的目的在于提供一种用于室温钠硫电池的一维氮化钼/二维氮化钒异质结(1D MoN/2D VN)材料及其制备方法,解决现有氮化物异质结结构可控性差、界面耦合程度低等问题,实现具有可控一维/二维耦合结构的氮化物异质结材料的可控制备,
[0023]相对于现有技术,本发明的有益效果:本发明构建的1D MoN/2D VN异质结具有丰富的异质界面,有利于界面电荷分布调节,降低反应能垒。将所述材料应用于室温钠硫电池中,负极端人工固态电解质界面(SEI)层可引导钠离子均匀沉积,抑制枝晶生长并改善固态电解质界面组成;正极端异质结添加剂对多硫化物具有吸附作用,且有助于降低Na2S生成能垒,促进多硫化物转化反应。所述材料用于改善室温钠硫电池中钠金属负极枝晶生长及硫正极多硫化物转化缓慢等问题。
Smart Images

Figure CN123017852A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of room temperature sodium-sulfur battery electrode materials technology, specifically to one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction 1D MoN / 2D VN, its preparation method, and its application in room temperature sodium-sulfur batteries. Technical Background
[0002] Room-temperature sodium-sulfur batteries possess advantages such as abundant sulfur resources, high theoretical specific capacity, and low cost, but several problems still exist in practical applications. Sodium metal anodes are prone to dendrite formation during deposition / stripping, leading to reduced safety. Simultaneously, the unstable solid-state electrolyte interface causes continuous electrolyte consumption, affecting cycle performance. Sulfur cathodes generate soluble polysulfides (Na₂S₂) during the reaction process. n (2≤n≤8), which easily leads to shuttle, causing loss of active material and capacity decay. The formation and conversion process of Na2S is relatively slow, which also limits the rate performance of the battery.
[0003] To address these issues, existing technologies employ transition metal nitrides to modulate the positive and negative electrode interfaces of sodium-sulfur batteries. Their excellent conductivity, catalytic activity, and stability help promote polysulfide conversion and stabilize sodium metal deposition. However, the construction of nitride heterostructures typically involves a multi-component synergistic nitriding process. Difficulties exist in matching nitriding temperatures, reaction kinetics, and phase transformation processes among different metal oxide precursors, making the controllable preparation of heterostructures still quite challenging. Currently, there are reports on 1D MoN / 2D V2O3 oxide-nitride composite structures (JI D, LI H, DU T, et al. Synthesizing 1D Molybdenum / 2D Vanadium-Based Heterostructures for ZincBatteries [J]. ACS Applied Energy Materials, 2025, 8(22): 16610-20.). However, the controllable preparation of 1DMoN / 2D VN all-nitride heterostructures still presents significant challenges, with key issues including precursor structure preservation, synchronous transformation during high-temperature nitriding, and the formation of stable heterostructure interfaces.
[0004] For example, vanadium nitride can regulate sodium deposition and stripping, thereby improving the stability of sodium anodes (XIA X, LV X, YAOY, et al. A sodiophilic VN interlayer stabilizing a Na metal anode [J]. Nanoscale Horizons, 2022, 7(8): 899-907). Molybdenum nitride can not only promote polysulfide conversion reactions, but also induce uniform sodium ion deposition, thereby improving the interfacial stability of sodium metal anodes (LI Z, WANG C, LING F, et al. Room-Temperature Sodium–Sulfur Batteries: Rules for Catalyst Selection and Electrode Design [J]. Advanced Materials, 2022, 34(32): 2204214.). However, single materials are difficult to balance adsorption capacity and catalytic performance, and the overall regulation effect is limited. Some studies have improved interfacial properties by constructing heterostructures, but existing technologies mostly focus on single electrode processes, and there is insufficient synergistic regulation of sodium anode deposition behavior and sulfur cathode reaction process, and the structural design is relatively simple.
[0005] Therefore, it is necessary to provide a nitride heterojunction material with stable structure and tight interfacial bonding to simultaneously improve sodium deposition behavior and polysulfide conversion process, thereby enhancing the overall performance of room temperature sodium-sulfur batteries. Summary of the Invention
[0006] The purpose of this invention is to provide a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction (1D MoN / 2D VN) material for room-temperature sodium-sulfur batteries and its preparation method, solving the problems of poor structural controllability and low interfacial coupling in existing nitride heterojunctions, and realizing the controllable preparation of nitride heterojunction materials with controllable one-dimensional / two-dimensional coupling structures.
[0007] Another objective of this invention is to provide the application of the aforementioned one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction material in room-temperature sodium-sulfur batteries. The heterojunction material can be used simultaneously for sodium metal anode interface modification and sulfur cathode functionalization modification. On the anode side, it can regulate the uniform deposition of sodium ions, inhibit sodium dendrite growth, and promote the formation of a stable solid electrolyte interface layer. On the cathode side, it can enhance the adsorption and catalytic conversion capabilities of polysulfides, suppress the shuttle effect, and improve the utilization rate of sulfur active materials, effectively improving the cycle stability, rate performance, and long cycle life of room-temperature sodium-sulfur batteries.
[0008] To achieve the above objectives, this invention provides a method for preparing a 1D MoN / 2D VN heterojunction material for room-temperature sodium-sulfur batteries. A vanadium source and a molybdenum source are dissolved in deionized water to form a homogeneous solution under the action of hydrogen peroxide. Subsequently, vanadium oxide gel and molybdenum oxide gel are obtained through a solvothermal reaction. The two gels are mixed and stirred uniformly, and then freeze-dried to obtain a 1D MoO3 / 2D V2O5·1.6 H2O heterostructure precursor. Under inert gas protection, a nitrogen-containing atmosphere is generated through the thermal decomposition of a nitrogen source to achieve in-situ nitridation transformation of the oxide precursor, yielding the 1D MoN / 2D VN heterojunction material. The specific steps are as follows:
[0009] (a) Dissolve the vanadium source in deionized water and stir to obtain solution A; at the same time, dissolve the molybdenum source in deionized water and stir to obtain solution B;
[0010] (b) Add an oxidant to solution A and solution B respectively to carry out a complexation reaction to obtain a precursor solution;
[0011] (c) The solution obtained in step (b) is transferred to a reaction vessel for a solvothermal reaction. After the reaction is completed, it is naturally cooled to room temperature to obtain vanadium oxide gel and molybdenum oxide gel, respectively.
[0012] (d) The vanadium oxide gel and molybdenum oxide gel were mixed and stirred to allow them to fully self-assemble. Then, the mixture was freeze-treated and freeze-dried to obtain a 1D MoO3 / 2D V2O5·1.6 H2O heterostructure precursor.
[0013] (e) The precursor and nitrogen source are placed in a tube furnace and heat-treated under inert gas protection to achieve in-situ nitriding conversion and obtain 1D MoN / 2D VN heterojunction material.
[0014] Further, in step (a), the vanadium source is selected from one or more of vanadium pentoxide, ammonium metavanadate, or vanadium trichloride, and the molybdenum source is selected from one or two of molybdenum trioxide or ammonium molybdate; the concentrations of solution A and solution B are 10~100 mmol L⁻ 1 .
[0015] Further, in step (b), the oxidant is hydrogen peroxide, with a mass fraction of 20-30%, used to promote the dissolution and complexation of the precursor. The molar ratio of the hydrogen peroxide to the metal elements in the vanadium and molybdenum sources is (50-200):1.
[0016] Further, in step (c), the solvothermal reaction temperature is 160~200 °C, and the reaction time is 4~10 h.
[0017] Further, in step (d), the stirring time is 24~72 h; the freezing temperature is −10~−20 ℃, the freezing time is 8~24 h; and the freeze-drying time is 24~48 h.
[0018] Further, the nitrogen source in step (e) includes one or more of urea, ammonia, or other nitrogen-containing organic compounds; the inert atmosphere is argon or nitrogen, the heat treatment temperature is 600~800℃, and the heating rate is 2~10℃·min⁻ 1 The heat preservation time is 1~4 hours.
[0019] Furthermore, when the nitrogen source is a solid nitrogen source, the molar ratio of the nitrogen source to the precursor is (10~100):1, and the flow rate of the inert atmosphere is 3~15 sccm; when the nitrogen source is ammonia, the ammonia and the inert atmosphere are introduced into the reaction system as a mixed gas, wherein the volume percentage of ammonia in the mixed gas is 70%, and the flow rate of the mixed gas is 50~300 mL·min⁻ 1 .
[0020] Further, in step (e), the heat treatment process is carried out under the protection of an inert gas, which is argon or nitrogen, and the gas flow rate is 3 to 15 sccm; by adjusting the inert gas flow rate, the concentration of nitrogen-containing active atmosphere in the furnace can be controlled, thereby adjusting the degree of nitriding of the material and the composition of the product.
[0021] Furthermore, in step (e), when the inert gas flow rate is 3 to 15 sccm, the lower gas flow rate is beneficial to maintaining the nitrogen-containing active atmosphere generated by the thermal decomposition of the nitrogen source in the furnace, thereby promoting the nitriding reaction; when the inert gas flow rate is 15 to 30 sccm, the nitrogen-containing active gas is quickly carried away, resulting in a weakening of the nitriding reaction, which is not conducive to the formation of products with a high degree of nitriding.
[0022] This invention also provides the application of a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction as a functional additive for the positive electrode of a room-temperature sodium-sulfur battery and an interface modification material for the sodium metal negative electrode. The method includes the following steps: loading the 1D MoN / 2D VN heterojunction material onto the surface of a sodium metal negative electrode via mechanical rolling to construct a modified sodium negative electrode; simultaneously, introducing the 1D MoN / 2D VN heterojunction material as a functional additive into a sulfur positive electrode to construct a modified sulfur positive electrode. Specifically: uniformly spreading the 1D MoN / 2D VN heterojunction material onto the surface of a sodium metal foil, and after mechanical rolling and pressing, allowing it to stand at room temperature to form a stable artificial solid electrolyte interface layer, thus obtaining a modified sodium metal negative electrode; simultaneously, adding a sulfur / porous carbon composite material, a conductive agent, the 1D MoN / 2D VN heterojunction material, and a binder into N-methylpyrrolidone to form a slurry, which is then coated onto the surface of an aluminum foil current collector. After vacuum drying, a room-temperature sodium-sulfur battery sulfur positive electrode is obtained, thereby achieving synergistic modification of both the positive and negative electrodes of the sodium-sulfur battery.
[0023] Compared to existing technologies, the beneficial effects of this invention are as follows: The 1D MoN / 2D VN heterojunction constructed by this invention has abundant heterojunction interfaces, which is beneficial for regulating the interface charge distribution and reducing the reaction energy barrier. When applied to room-temperature sodium-sulfur batteries, the artificial solid electrolyte interphase (SEI) layer at the negative electrode can guide the uniform deposition of sodium ions, inhibit dendrite growth, and improve the composition of the solid electrolyte interface; the heterojunction additive at the positive electrode has an adsorption effect on polysulfides and helps to reduce the Na2S formation energy barrier, promoting the polysulfide conversion reaction. This material is used to improve problems such as dendrite growth at the sodium metal negative electrode and slow polysulfide conversion at the sulfur positive electrode in room-temperature sodium-sulfur batteries.
[0024] The 1D MoN / 2D VN heterojunction material obtained by this invention has good conductivity and catalytic activity, and can be applied to the synergistic regulation of the positive and negative electrode interfaces of room temperature sodium-sulfur batteries, significantly improving the cycle stability, rate performance and long cycle life of the battery, showing good electrochemical performance and broad application prospects. Attached Figure Description
[0025] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the 1D MoN / 2D VN heterojunction material prepared in Example 1 of this invention.
[0026] Figure 2 To illustrate Comparative Example 1 of this invention, different inert carrier gas flow rates were controlled to control the ammonia atmosphere, resulting in XRD patterns of heterojunction materials with different degrees of nitridation.
[0027] Figure 3 This is a scanning electron microscope (SEM) image of the 1D MoN / 2D VN heterojunction material prepared in Example 1 of the present invention;
[0028] Figure 4 The elemental mapping (EDS) diagram of the 1D MoN / 2D VN heterojunction material prepared in Example 1 of this invention;
[0029] Figure 5 Transmission electron microscope (TEM) image of the 1D MoN / 2D VN heterojunction material prepared in Example 1 of this invention;
[0030] Figure 6 The time-voltage curves are for assembling a Na||Na symmetric cell with the modified sodium anode prepared in Example 1 of the present invention and the bare sodium anode in Comparative Example 1.
[0031] Figure 7 Tafel curves for the modified sodium anodes of Comparative Example 1 and Application Example 1;
[0032] Figure 8 SEM images of sodium deposition on the modified sodium anodes of Comparative Example 1 and Application Example 1;
[0033] Figure 9 Time-mass specific capacity curves for room temperature sodium-sulfur batteries assembled using Comparative Examples 1 and 2 and Application Examples 1 and 2;
[0034] Figure 10 For testing the rate performance of room temperature sodium-sulfur batteries assembled using Comparative Examples 1 and 2 and Application Examples 1 and 2;
[0035] Figure 11 Long-cycle performance testing of room-temperature sodium-sulfur batteries assembled using Comparative Examples 1 and 2 and Application Examples 1 and 2;
[0036] Figure 12 The ion diffusion coefficient of the room temperature sodium-sulfur batteries assembled using Comparative Examples 1 and 2 and Application Examples 1 and 2 was tested.
[0037] Figure 13 Cyclic voltammetry (CV) tests were conducted on the room-temperature sodium-sulfur batteries assembled using Comparative Examples 1 and 2 and Application Examples 1 and 2.
[0038] Figure 14 In-situ impedance testing of room temperature sodium-sulfur batteries assembled using Comparative Examples 1 and 2 and Application Examples 1 and 2. Detailed Implementation
[0039] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention, but the implementation of the present invention is not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] Example 1
[0041] The preparation method of the one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction in this embodiment is as follows:
[0042] (a) Dissolve 0.36 g (2 mmol) of V₂O₅ in 25 ml of deionized water and stir to obtain a concentration of 80 mmol L⁻ 1 Solution A; simultaneously, 0.28 g (2 mmol) of MoO3 was dissolved in 25 ml of deionized water and stirred to obtain a solution with a concentration of 80 mmol / L. 1 Solution B;
[0043] (b) Add 20 mL of 30% hydrogen peroxide to solution A and solution B respectively to carry out a complexation reaction to obtain precursor suspension A and precursor suspension B;
[0044] (c) The solution obtained in step (b) was transferred to a reaction vessel and reacted at 170°C for 5 h to carry out a solvothermal reaction. After the reaction was completed, it was naturally cooled to room temperature to obtain vanadium oxide gel and molybdenum oxide gel, respectively.
[0045] (d) The obtained vanadium oxide gel was mixed with molybdenum oxide gel and stirred for 24 h to allow it to fully self-assemble. Then, it was frozen at -10℃ for 12 h and freeze-dried for 24 h to obtain a 1D MoO3 / 2D V2O5·1.6 H2O heterostructure precursor.
[0046] (e) 0.7 g (3.9 mmol) of the obtained 1DMoO3 / 2DV2O5·1.6H2O heterostructure precursor and 5 g (83 mmol) of urea were placed in a tube furnace, with two porcelain boats placed in the furnace, urea in front and the precursor behind. The furnace was then heat-treated under an inert argon atmosphere at a temperature of 600 °C, an argon flow rate of 5 sccm, and a heating rate of 5 °C·min⁻¹. 1 The heat treatment time was 3 h to achieve in-situ nitridation transformation and obtain 1D MoN / 2D VN heterojunction material.
[0047] Structural and morphological characterization
[0048] The crystalline phase analysis of the 1D MoN / 2D VN heterostructure material prepared in Example 1 was performed using X-ray diffraction (XRD), and the results are as follows: Figure 1As shown in the figure, the obtained sample exhibits characteristic diffraction peaks corresponding to both MoN and VN. The diffraction peaks located near approximately 37°, 43°, 63°, and 75° correspond to the VN crystal structure (PDF#35-0768), while the diffraction peaks located near approximately 37°, 43°, 50°, and 74° belong to the MoN crystal phase (PDF#25-1367). These results demonstrate that the oxide precursor was successfully transformed into a MoN / VN dual-phase heterostructure material after nitriding treatment.
[0049] The microstructure of the material was observed using a scanning electron microscope (SEM), such as... Figure 3 As shown in the figure, the obtained material exhibits a distinct one-dimensional / two-dimensional composite structure. Numerous one-dimensional nanoribbon structures with high aspect ratios are uniformly distributed on the surface of the two-dimensional sheet structure, forming a continuous, interwoven network structure. This unique structure effectively increases the specific surface area of the material and provides abundant interfacial regions.
[0050] Further analysis of elemental distribution was performed using energy-dispersive X-ray spectroscopy (EDS), such as... Figure 4 As shown in the figure, the results show that N, V, and Mo elements are uniformly distributed throughout the material region, with V and Mo elements maintaining a highly uniform spatial distribution. This indicates that the MoN and VN components achieve uniform coupling during the composite process, forming a stable heterostructure.
[0051] The crystal structure of the material was further analyzed using transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM), such as... Figure 5 As shown, clear lattice fringes can be observed in the HRTEM image, with interplanar spacings of approximately 0.25 nm and 0.21 nm, corresponding to the (200) crystal planes of MoN and VN, respectively, proving that the MoN and VN crystal phases form a closely contacted heterostructure interface at the nanoscale. Selected area electron diffraction (SAED) patterns simultaneously show diffraction rings corresponding to MoN and VN, further verifying the successful construction of the 1D MoN / 2D VN heterostructure.
[0052] Comparative Examples 1-3
[0053] The difference between Comparative Examples 1-3 and Examples 1-3 is that the inert gas flow rate is 15 sccm, 20 sccm, and 30 sccm, respectively, while other operations are the same as in Example 1.
[0054] like Figure 2As shown, with the decrease of inert carrier gas flow rate, the characteristic peak of V2O3 in the sample gradually weakens, while the characteristic peaks of MoN and VN gradually strengthen. When the inert carrier gas flow rate is high, the residence time of ammonia in the reaction region is short, resulting in incomplete nitriding reaction; after reducing the inert carrier gas flow rate, the ammonia atmosphere is effectively maintained, promoting the complete nitriding of the oxide precursor and forming a MoN / VN heterostructure.
[0055] When the inert gas flow rate is 3–15 sccm, the lower gas flow rate is beneficial to maintaining the nitrogen-containing active atmosphere generated by the thermal decomposition of nitrogen source in the furnace, thereby promoting the nitriding reaction. When the inert gas flow rate is 15–30 sccm, the nitrogen-containing active gas is quickly carried away, resulting in a weakening of the nitriding reaction and hindering the formation of products with a high degree of nitriding.
[0056] Example 2
[0057] The preparation method of the one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction in this embodiment is as follows:
[0058] (a) Dissolve 0.36 g (2 mmol) of V₂O₅ in 25 ml of deionized water and stir to obtain a concentration of 80 mmol L⁻ 1 Solution A; simultaneously, 0.28 g (2 mmol) of MoO3 was dissolved in 25 ml of deionized water and stirred to obtain a solution with a concentration of 80 mmol / L. 1 Solution B;
[0059] (b) Add 20 mL of 30% hydrogen peroxide to solution A and solution B respectively to carry out a complexation reaction to obtain the precursor solution;
[0060] (c) The solution obtained in step (b) was transferred to a reaction vessel and reacted at 170°C for 5 h for a solvothermal reaction. After the reaction was completed, it was naturally cooled to room temperature to obtain vanadium oxide gel and molybdenum oxide gel, respectively.
[0061] (d) The vanadium oxide gel obtained in step (c) was mixed with the molybdenum oxide gel and stirred for 24 h to allow it to fully self-assemble. Then, it was frozen at -10℃ for 15 h and freeze-dried for 36 h to obtain a 1D MoO3 / 2D V2O5·1.6 H2O heterostructure precursor.
[0062] (e) The obtained 1D MoO3 / 2D V2O5·1.6 H2O heterostructure precursor was placed in a tube furnace, and an argon-ammonia mixture (ammonia volume percentage 70%) was introduced into the reaction system for heat treatment at a flow rate of 100 mL·min⁻. 1 The heat treatment temperature is 650℃, and the heating rate is 2℃·min⁻ 1The heat treatment time was 4 h to achieve in-situ nitridation transformation and obtain 1D MoN / 2D VN heterojunction material.
[0063] In-situ nitriding transformation yields 1D MoN / 2D VN heterojunction materials.
[0064] Example 3
[0065] The preparation method of the one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction in this embodiment is as follows:
[0066] (a) Dissolve 0.36 g (2 mmol) of V₂O₅ in 25 ml of deionized water and stir to obtain a concentration of 80 mmol L⁻ 1 Solution A; simultaneously, 0.28 g (2 mmol) of MoO3 was dissolved in 25 ml of deionized water and stirred to obtain a solution with a concentration of 80 mmol / L. 1 Solution B;
[0067] (b) Add 20 mL of 30% hydrogen peroxide to solution A and solution B respectively to carry out a complexation reaction to obtain the precursor solution;
[0068] (c) The solution obtained in step (b) was transferred to a reaction vessel and reacted at 190°C for 4 h for a solvothermal reaction. After the reaction was completed, it was naturally cooled to room temperature to obtain vanadium oxide gel and molybdenum oxide gel, respectively.
[0069] (d) The vanadium oxide gel obtained in step (c) was mixed with the molybdenum oxide gel and stirred for 36 h to allow it to fully self-assemble. Then, it was frozen at -15℃ for 10 h and freeze-dried for 30 h to obtain a 1D MoO3 / 2D V2O5·1.6 H2O heterostructure precursor.
[0070] (e) The obtained precursor and 5 g of urea were placed in a tube furnace and heat-treated under inert nitrogen atmosphere at a temperature of 700 °C, a nitrogen flow rate of 5 sccm, and a heating rate of 8 °C·min⁻¹. 1 The heat treatment time was 3 h to achieve in-situ nitridation transformation and obtain 1D MoN / 2D VN heterojunction material.
[0071] Example 4
[0072] The preparation method of the one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction in this embodiment is as follows:
[0073] (a) Dissolve 0.36 g (2 mmol) of V₂O₅ in 25 ml of deionized water and stir to obtain a concentration of 80 mmol L⁻ 1Solution A; simultaneously, 0.28 g (2 mmol) of MoO3 was dissolved in 25 ml of deionized water and stirred to obtain a solution with a concentration of 80 mmol / L. 1 Solution B;
[0074] (b) Add 20 mL of 30% hydrogen peroxide to solution A and solution B respectively to carry out a complexation reaction to obtain the precursor solution;
[0075] (c) The solution obtained in step (b) was transferred to a reaction vessel and reacted at 170°C for 5 h to carry out a solvothermal reaction. After the reaction was completed, it was naturally cooled to room temperature to obtain vanadium oxide gel and molybdenum oxide gel, respectively.
[0076] (d) The vanadium oxide gel obtained in step (c) was mixed with the molybdenum oxide gel and stirred for 48 h to allow it to fully self-assemble. Then, it was frozen at -20℃ for 8 h and freeze-dried for 48 h to obtain a 1D MoO3 / 2D V2O5·1.6 H2O heterostructure precursor.
[0077] (e) The obtained precursor and 5 g of urea were placed in a tube furnace and heat-treated under the protection of inert argon gas at a temperature of 800 °C, an argon flow rate of 5 sccm, and a heating rate of 10 °C·min⁻⁻⁻⁻⁶. 1 The heat treatment time was 2 h to achieve in-situ nitridation transformation and obtain 1D MoN / 2D VN heterojunction material.
[0078] Application Example 1
[0079] Sodium metal anode material with an artificial SEI layer constructed from the 1D MoN / 2D VN heterojunction material obtained in Example 1 is used. The anode material consists of metallic sodium and a 1D MoN / 2D VN heterojunction artificial SEI layer supported on its surface. The preparation process specifically includes the following steps:
[0080] (1) The 1D MoN / 2D VN heterojunction material powder is uniformly spread on the surface of sodium metal foil and compacted by mechanical rolling, with the number of rolling cycles being 15 to 25.
[0081] (2) Apply 4-6 kg pressure to the rolled sodium foil for tableting and let it stand at room temperature for 24 h to form a stable interface layer;
[0082] (3) Remove excess unbonded powder from the surface of sodium foil to obtain a sodium metal anode with an artificial SEI layer on the surface;
[0083] (4) Cut the obtained composite sodium foil into electrode sheets with a diameter of 12 mm;
[0084] (5) The above operations are carried out in a glove box filled with inert gas, and the water and oxygen content is controlled below 0.1 ppm.
[0085] Application Example 2
[0086] The 1D MoN / 2D VN heterojunction material obtained in Example 1 was introduced into the sulfur cathode as a functional additive to construct a modified sulfur cathode. The preparation method includes the following steps:
[0087] (1) Weigh the following by mass ratio: 70 wt.% sulfur / porous carbon composite material, 17 wt.% conductive agent, 3 wt.% 1DMoN / 2D VN heterojunction material and 10 wt.% binder;
[0088] (2) Add the above components to N-methylpyrrolidone solvent and mix and stir to form a slurry;
[0089] (3) The obtained slurry is uniformly coated on the surface of the aluminum foil current collector, and the coating thickness is controlled to be uniform;
[0090] (4) The electrode sheet is vacuum dried at 50-70 °C for 10-15 h to obtain a sulfur positive electrode sheet;
[0091] (5) Cut the dried electrode sheet into a circular piece with a diameter of 12 mm for use as the positive electrode of the battery;
[0092] (6) The loading of the positive electrode active material is 0.8–1.5 mg·cm⁻ 2 ;
[0093] (7) The above preparation process is carried out in a dry environment.
[0094] Comparative Example 1
[0095] Fresh sodium foil was cut into electrode sheets with a diameter of 12 mm to serve as unmodified sodium anodes. The above operations were performed in an inert gas glove box with water and oxygen contents both below 0.1 ppm. A sodium metal anode without an artificial SEI layer was prepared using a method essentially the same as in Example 1, except that a 1D MoN / 2D VN heterojunction material was not introduced onto the sodium foil surface; the remaining rolling and pressing conditions were the same.
[0096] Comparative Example 2
[0097] A sulfur cathode without heterojunction material is prepared in a manner similar to that in Application Example 2, except that no 1D MoN / 2D VN heterojunction material is added to the cathode slurry. The cathode consists of 70 wt.% sulfur / porous carbon composite material, 20 wt.% conductive agent, and 10 wt.% binder.
[0098] Test Example 1
[0099] A Na||Na symmetric cell was assembled using the sodium anode described in Comparative Example 1 and Application Example 1. The electrolyte was 1.0 M NaPF6 (EC:DEC = 1:1, volume ratio) with 5% FEC added, and the separator was glass fiber. Constant current cycling tests were conducted at 25 °C with a current density of 1 mA·cm⁻¹. 2 The deposition / stripping capacity is 1 mAh·cm⁻ 2 .
[0100] The results show that: Figure 6 As shown, the unmodified sodium anode symmetric cell exhibits significant polarization and fails after approximately 60–70 hours of cycling; the symmetric cell modified with a heterojunction interface layer achieves a cycling time exceeding 950 hours under the same conditions, demonstrating significantly improved cycling stability.
[0101] Test Example 2
[0102] Na||Na symmetric cells were assembled using the sodium anodes described in Comparative Example 1 and Application Example 1. Under the same electrolyte and test conditions, the exchange current density was measured using an electrochemical workstation at a scan rate of 10 mV·s⁻ 1 .
[0103] The results show that, as shown in Figure 7, the exchange current density of the modified electrode is 0.42 mA·cm⁻. 2 This is higher than the 0.05 mA·cm⁻ of the unmodified electrode. 2 The significant increase in exchange current density indicates that the heterojunction modification layer can effectively reduce the charge transfer impedance of sodium ions at the electrode / electrolyte interface, accelerate the interfacial reaction kinetics, and promote the uniform deposition and stripping of sodium ions.
[0104] Test Example 3
[0105] Using the sodium anodes described in Comparative Example 1 and Application Example 1, Na||Na symmetric cells were assembled. Under the same electrolyte conditions, at 1 mA cm⁻ 2 Under current density conditions, at 1, 3 and 5 mAh cm⁻ 2 Sodium deposition / stripping tests were conducted to assess the deposition capacity. After the tests, the cells were disassembled, and scanning electron microscopy was used to observe the changes in the surface morphology of the sodium anode under different deposition capacities.
[0106] The results, as shown in Figure 8, indicate that the 1D MoN / 2D VN heterojunction modified sodium anode maintains a relatively uniform and dense surface structure under different deposition capacity conditions, even at 5 mAh cm⁻. 2At higher deposition capacities, no obvious dendrites or large-sized particle accumulation appeared on the electrode surface, indicating that the heterojunction structure can effectively induce uniform sodium deposition and alleviate local current concentration. In contrast, with increasing deposition capacity, the bare sodium anode gradually showed obvious loose accumulation and irregular particle structure on the surface, especially at 5 mAh cm⁻¹. 2 The formation of numerous rough dendritic deposits under these conditions indicates severe sodium dendrite growth and interfacial instability. This demonstrates that the 1D MoN / 2D VN heterojunction can effectively regulate sodium ion deposition behavior, reduce dendrite growth tendency, and enhance the interfacial stability of the sodium metal anode under high-capacity deposition conditions.
[0107] Test Example 4
[0108] A room-temperature sodium-sulfur battery, namely MoN / VN−Na||MoN / VN−S, was assembled using the sodium anode described in Application Example 1 and the sulfur cathode described in Application Example 2. A Na||S battery was assembled using an unmodified sodium anode (Comparative Example 1) and a sulfur cathode without heterojunction material (Comparative Example 2). The electrolyte was 2 M NaTFSI (PC:FEC = 1:1, volume ratio), and the separator was glass fiber. Cyclic tests were conducted at 25 °C.
[0109] The results show that: Figure 9 As shown, the battery using heterojunction materials has a specific capacity of approximately 710 mAh·g⁻ after 100 cycles. 1 This is higher than the 430 mAh·g⁻ of the comparative battery. 1 Cyclic stability is improved.
[0110] Test Example 5
[0111] A room-temperature sodium-sulfur battery, namely MoN / VN−Na||MoN / VN−S, was assembled using the sodium anode described in Application Example 1 and the sulfur cathode described in Application Example 2. A Na||S battery was assembled using an unmodified sodium anode (Comparative Example 1) and a sulfur cathode without heterojunction material (Comparative Example 2). Rate testing was conducted under the same electrolyte and testing conditions.
[0112] The results show that: Figure 10 As shown, the MoN / VN−Na||MoN / VN−S battery exhibits higher reversible capacity and superior rate performance under different rate conditions. At 0.1 C, 0.2 C, 0.5 C, 1 C, and 2 C, the battery maintains a high capacity output; when the rate recovers to 0.2 C, its specific capacity recovers to approximately 950 mAh·g⁻. 1 This demonstrates excellent structural stability and electrochemical reversibility. In contrast, the comparative Na||S battery exhibits rapid capacity decay with increasing rate, decreasing to approximately 150 mAh·g⁻ at 2 C. 1Furthermore, the capacity recovery is limited after returning to 0.2 C. These results indicate that the 1D MoN / 2D VN heterojunction can effectively promote electron / ion transport, reduce polarization, improve sulfur species conversion kinetics, and enhance the rate performance of room-temperature sodium-sulfur batteries.
[0113] Test Example 6
[0114] A room-temperature sodium-sulfur battery, namely MoN / VN−Na||MoN / VN−S, was assembled using the sodium anode described in Application Example 1 and the sulfur cathode described in Application Example 2. A Na||S battery was assembled using an unmodified sodium anode (Comparative Example 1) and a sulfur cathode without heterojunction material (Comparative Example 2). Long-term cycle performance was tested at 0.5 C rate under the same electrolyte and test conditions.
[0115] The results show that: Figure 11 As shown, the MoN / VN−Na||MoN / VN−S battery retains approximately 480 mAh·g⁻ after 400 cycles at 0.5 C. 1 The reversible specific capacity is significantly higher than that of the comparative Na||S battery by approximately 100 mAh·g⁻ 1 The capacity retention values indicate that the 1D MoN / 2D VN heterojunction can effectively stabilize the sodium metal anode interface, promote the reversible transformation of polysulfides, inhibit the loss of active materials, and improve the cycle stability of room temperature sodium-sulfur batteries.
[0116] Test Example 7
[0117] A room-temperature sodium-sulfur battery, namely MoN / VN−Na||MoN / VN−S, was assembled using the sodium anode described in Application Example 1 and the sulfur cathode described in Application Example 2. A Na||S battery was assembled using an unmodified sodium anode (Comparative Example 1) and a sulfur cathode without heterojunction material (Comparative Example 2). Intermittent galvanostatic titration (GITT) was performed under the same electrolyte and test conditions to analyze the battery reaction kinetics and Na⁺ diffusion behavior.
[0118] The results show that: Figure 12 As shown in (a), the MoN / VN−Na||MoN / VN−S battery exhibits smaller voltage polarization and a more stable plateau characteristic during charge and discharge, indicating a significant improvement in its interfacial reaction kinetics. Furthermore, from Figure 12 (b, c) shows that during the charging and discharging process, the Na⁺ diffusion coefficient of the MoN / VN−Na||MoN / VN−S battery is generally higher than that of the comparative Na||S battery, indicating that the heterojunction structure can effectively promote sodium ion transport and reduce ion diffusion resistance.
[0119] Test Example 8
[0120] A room-temperature sodium-sulfur battery, namely MoN / VN−Na||MoN / VN−S, was assembled using the sodium anode described in Application Example 1 and the sulfur cathode described in Application Example 2. A Na||S battery was assembled using an unmodified sodium anode (Comparative Example 1) and a sulfur cathode without heterojunction material (Comparative Example 2). Cyclic voltammetry (CV) tests were performed at different scan rates under the same electrolyte and test conditions to analyze the electrochemical reaction kinetics of the batteries.
[0121] The results show that: Figure 13 As shown in (a, c), as the scan rate increases from 0.1 mV s⁻ 1 Increased to 0.8 mV s⁻ 1 Both types of batteries showed a gradual increase in redox peak current, but the MoN / VN−Na||MoN / VN−S battery consistently exhibited a higher peak current response and a smaller peak position shift, indicating that it possesses faster redox reaction kinetics and lower electrochemical polarization. Furthermore, from Figure 13 As shown in (b, d), based on the fitting relationship between peak current and scan rate, the b values for the MoN / VN−Na||MoN / VN−S battery reach 0.57 and 0.86, respectively, both higher than the 0.53 and 0.52 of the comparative Na||S battery. This indicates that the electrode system modified with heterojunction has a more significant pseudocapacitive contribution and faster interfacial charge transport capability. These results demonstrate that the 1D MoN / 2D VN heterojunction can effectively promote electron / ion co-transport and accelerate polysulfide conversion reactions, thereby improving the electrochemical reaction kinetics performance of room-temperature sodium-sulfur batteries.
[0122] Test Example 9
[0123] A room-temperature sodium-sulfur battery, namely MoN / VN−Na||MoN / VN−S, was assembled using the sodium anode described in Application Example 1 and the sulfur cathode described in Application Example 2. A Na||S battery was assembled using an unmodified sodium anode (Comparative Example 1) and a sulfur cathode without heterojunction material (Comparative Example 2). In-situ electrochemical impedance spectroscopy (EIS) was performed under the same electrolyte and testing conditions to study the interface evolution and reaction kinetics behavior of the battery during charge and discharge.
[0124] The results show that: Figure 14 As shown in (a, b), the semicircle diameter of the impedance spectrum of the MoN / VN−Na||MoN / VN−S cell is significantly smaller than that of the comparative Na||S cell at different charge and discharge potentials, indicating that it has lower interfacial charge transfer impedance and better ion transport capability. Figure 14The two-dimensional relaxation time distribution heatmaps shown in (c, d) exhibit a smoother change, indicating greater interfacial stability during battery cycling. These results demonstrate that the 1D MoN / 2D VN heterojunction can synergistically optimize the interfacial film structure, promote charge transfer, and enhance ion diffusion, thereby significantly improving the interfacial stability and sulfur cathode electrochemical reaction kinetics of room-temperature sodium-sulfur batteries.
[0125] This invention achieves synergistic regulation of the positive and negative electrodes of a room-temperature sodium-sulfur battery by constructing a 1D MoN / 2D VN heterojunction artificial SEI layer on the surface of metallic sodium and using this material in a sulfur cathode. This structure facilitates uniform sodium deposition and improves interfacial stability, while also promoting polysulfide conversion reactions, thereby enhancing the battery's cycle stability and capacity retention.
[0126] In summary, the above embodiments are only used to illustrate the technical principles and implementation methods of the present invention, enabling those skilled in the art to understand and implement the present invention, and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, or improvements made to the present invention without departing from the spirit and substance of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction, characterized in that, Includes the following steps: (1) Dissolve the vanadium source in deionized water and stir to obtain solution A; dissolve the molybdenum source in deionized water and stir to obtain solution B; (2) Add oxidant to solution A and solution B respectively to react and obtain precursor suspension A and precursor suspension B; (3) The precursor suspension A and precursor suspension B obtained in step (2) are subjected to solvothermal reactions to obtain vanadium oxide gel and molybdenum oxide gel, respectively. (4) The vanadium oxide gel and molybdenum oxide gel were mixed and stirred at a molar ratio of 1:1, and then subjected to freezing and freeze-drying treatment to obtain a 1D MoO3 / 2D V2O5·1.6 H2O heterostructure precursor; (5) The precursor obtained in step (4) and the nitrogen source are heat-treated in an inert atmosphere to achieve in-situ nitridation conversion and obtain a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction material.
2. The method for preparing a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction according to claim 1, characterized in that, The vanadium source in step (1) is one or more of vanadium pentoxide, ammonium metavanadate, or vanadium trichloride; the molybdenum source is one or two of molybdenum trioxide or ammonium molybdate; the concentration of solution A is 10~100 mmol L⁻ 1 The concentration of solution B is 10~100 mmol / L⁻ 1 .
3. The method for preparing a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction according to claim 1, characterized in that, The oxidant in step (2) is hydrogen peroxide, with a mass fraction of 20-30%, and the molar ratio of hydrogen peroxide to the metal elements in the vanadium and molybdenum sources is (50-200):
1.
4. The method for preparing a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction according to claim 1, characterized in that, In step (3), the solvothermal reaction temperature is 160–200 °C and the time is 4–10 h.
5. The method for preparing a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction according to claim 1, characterized in that, In step (4), the stirring time is 24 to 72 h, the freezing temperature is −10 to −20 ℃, the freezing time is 8 to 24 h, and the freeze-drying time is 24 to 48 h.
6. The method for preparing a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction according to claim 1, characterized in that, The nitrogen source in step (5) includes one or more of urea, ammonia, or other nitrogen-containing organic compounds; the inert atmosphere is argon or nitrogen, the heat treatment temperature is 600~800℃, and the heating rate is 2~10℃·min⁻ 1 The heat preservation time is 1~4 hours.
7. The method for preparing a one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction according to claim 6, characterized in that, When the nitrogen source is a solid nitrogen source, the molar ratio of the nitrogen source to the precursor is (10~100):1, and the inert atmosphere gas flow rate is 3~15 sccm. When the nitrogen source is ammonia, ammonia and the inert atmosphere are introduced into the reaction system as a mixed gas, wherein ammonia accounts for 70% of the volume in the mixed gas, and the flow rate of the mixed gas is 50~300 mL·min⁻. 1 .
8. The one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction prepared by the preparation method according to any one of claims 1 to 7, characterized in that, A continuous interface contact structure is formed between the one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction (1D MoN / 2D VN).
9. The application of the one-dimensional molybdenum nitride / two-dimensional vanadium nitride heterojunction as described in claim 8 as a functional additive for the positive electrode of a room-temperature sodium-sulfur battery and an interface modification material for the sodium metal negative electrode.
10. The application according to claim 9, characterized in that, The process includes the following steps: loading the 1D MoN / 2D VN heterojunction material onto the surface of a sodium metal anode by mechanical rolling to construct a modified sodium anode; and simultaneously introducing the 1DMoN / 2D VN heterojunction material as a functional additive into a sulfur cathode to construct a modified sulfur cathode.
